(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
In this paper we introduce semi-normed difference operator triple sequence spaces by using a double Orlicz-functions, so we study their diﬀerent properties like completeness, solidity, monotonicity, symmetricity etc.